Multiple SNARE interactions of an SM protein: Sed5p/Sly1p binding is dispensable for transport - Peng, Renwang (Nature Publishing Group, 2004)
Sec1/Munc18 (SM) proteins are central to intracellular transport and neurotransmitter release but their exact role is still elusive. Several SM proteins, like the neuronal N-Sec1 and the yeast Sly1 protein, bind their cognate t-SNAREs with high affinity. This has been thought to be critical for their function. Here, we show that various mutant forms of Sly1p and the Golgi-localized syntaxin Sed5p, which abolish their high-affinity interaction, are fully functional in vivo, indicating that the tight interaction of the two molecules per se is not relevant for proper function. Mutant Sly1p unable to bind Sed5p is excluded from core SNARE complexes, also demonstrating that Sly1p function is not directly coupled to assembled SNARE complexes thought to execute membrane fusion. We also find that wild-type Sly1p and mutant Sly1p unable to bind Sed5p directly interact with selected ER-to-Golgi and intra-Golgi nonsyntaxin SNAREs. The newly identified, direct interactions of the SM protein with nonsytaxin SNAREs might provide a molecular mechanism by which SNAREs can be activated to engage in pairing and assemble into fusogenic SNARE complexes.